THE EFFECTS OF GLOBALIZATION ON IDENTITY - Hindi, Gizel (European Scientific Journal, ESJ, 2014)
The accelerating pace of globalization, the buzzword since 1990, is the cause of numerous socio-cultural complexities. Owing to globalization, literary texts have assumed a vital role to students’ communicative and critical awareness of the world around them. Globalization shares with postmodernism themes such as plurality and loss of identity in mediatic societies. Narratives are a motivational tool to not only achieve comprehension, but also experience the writers’ concern with contemporary issues. In the past, New Criticism boldly concluded that an objective analysis of text is feasible; however, the Reader Response theory advocated that readers interpret texts in relation to their own lives. Nonetheless, there are instances when a resistance to literary works occurs, particularly when conflicting cultural codes exist. Alienation— even self-effacement—could materialize consequent to attempting to create homogeneity and global solidarity. To postmodernists, meaning is no longer inherent in the text; the reader is involved in a quest to elucidate the textual material. In other words, intertextuality and deconstruction are at play since the content is a series of markings, and language is as an open system of signifiers that undermines the authority of words. With postmodernism, the reader is not a mere consumer but rather a ‘free’ interpreter of text; the printed matter is subject to a variety of interpretations. The effect of globalization on one’s identity is crucial to educated minds seeking enlightenment. In schools and universities, instructors ought to employ postmodern narratives in their language classes to suggest alternatives and pose queries concerning globalism.